2003
DOI: 10.1007/s00442-002-1114-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a simple plant morphological mutation on the arthropod community and the impacts of predators on a principal insect herbivore

Abstract: Plant features that enhance predator effectiveness can be considered extrinsic-resistance factors because they result in reduced insect herbivory. In this paper we test the hypothesis that reduced epicuticular wax (EW) in Pisum sativum L. is an extrinsic-resistance factor contributing to field resistance to Acyrthosiphon pisum (Harris). We monitored pea aphid populations in the field on reduced EW and normal EW near isolines of peas for two seasons and confirmed that aphid populations are lower on reduced EW p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 58 publications
6
34
1
Order By: Relevance
“…In North America, a complex of predators, parasitoids, and pathogens attacks the pea aphid (Fluke 1929). Several of these are more effective at capturing pea aphids on reduced wax peas (Eigenbrode et al 1998a, unpublished data;White and Eigenbrode 2000b;Rutledge et al 2003). The lady beetle Hippodamia convergens is the most abundant predator of aphids on the foliage of peas (White and Eigenbrode 2000a;Rutledge et al 2003) and more generally in the region of our study (Elberson 1992;Youssef 2000).…”
Section: Natural Historymentioning
confidence: 81%
See 2 more Smart Citations
“…In North America, a complex of predators, parasitoids, and pathogens attacks the pea aphid (Fluke 1929). Several of these are more effective at capturing pea aphids on reduced wax peas (Eigenbrode et al 1998a, unpublished data;White and Eigenbrode 2000b;Rutledge et al 2003). The lady beetle Hippodamia convergens is the most abundant predator of aphids on the foliage of peas (White and Eigenbrode 2000a;Rutledge et al 2003) and more generally in the region of our study (Elberson 1992;Youssef 2000).…”
Section: Natural Historymentioning
confidence: 81%
“…Plant wax had no direct effect on aphid density in the greenhouse, but fewer aphids were found on reduced wax plants in the 2002 field experiment. A previous experiment on reduced and normal wax pea found a trend toward poorer aphid survival on reduced wax pea in field clip cages (Rutledge et al 2003). Rutledge et al (2003) suggested that reduced wax peas suffer higher drought stress than normal peas, which could explain why reduced wax peas grew less rapidly than normal peas in 2002 (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Self-sustaining populations were first located near port cities rather than near release points (Day et al 1994;Wheeler and Stoops 1996). Coccinella septempunctata reached eastern Washington and northern Idaho in the early 1990s (Elberson 1992), and by 1998 C. septempunctata had almost completely replaced the native Coccinella species, with C. septempunctata representing 20-34% of the coccinellid community and C. transversoguttata less than 1% (Youssef 2000;White and Eigenbrode 2000;Rutledge et al 2003). However, the native H. convergens appeared to be more tolerant of C. septempunctata, and still represented 65-80% of the coccinellid community following invasion by C. septempunctata (Youssef 2000;White and Eigenbrode 2000).…”
Section: Methodsmentioning
confidence: 98%
“…Similarly, Eigenbrode et al (1998) showed that adult Hip. convergens foraged more effectively on pea cultivars with reduced epicuticular wax and Rutledge et al (2003) found that such cultivars hosted lower pea aphid populations in fi eld plots than isolines that lacked this trait. Comparing these isolines in cage and laboratory tests without predators revealed no differences between them in plant acceptance by aphids or their subsequent performance.…”
Section: Timing Of Arrival In Annual Cropsmentioning
confidence: 99%